Risk management of transboundary water resources using the green supply chain approach. (22nd December 2008) - Levner, Eugene; Alcaide Lopez de Pablo, David; Ganoulis, Jacques
The problem considered is the coordination of the ecological risks of all stakeholders in a transboundary river basin using the 'green' (environmental) Supply Chain (SC) approach. Using a combination of two managerial concepts – 'the environmental SC' and 'the house-of-quality' – a decision-making model that quantitatively estimates the integrated risk level is constructed. A mathematical model is proposed that allows the integrated risk to population and society in a transboundary river basin under geo-hydrological, economic, technological and social constraints to be mitigated.